THE QUALITY OF POPULATION ADMINISTRATION SERVICES IN THE TANGGULANGIN DISTRICT OF THE SIDOARJO PROVINCE - Amallia Khaula Yukiza; Hendra Sukmana (DIA: Jurnal Administrasi Publik, 2022)
This study seeks to assess the quality of population administration services in the Tanggulangin District of Sidoarjo Regency. In addition to understanding the elements that promote and impede service in Tanggulangin District, Sidoarjo Regency. Employing descriptive qualitative methodologies. Using observation, interviews, and documentation, data was obtained. This study's data analysis consists of three components: data reduction, data display, and deriving conclusions. The findings of this study indicate that the quality of public service delivery in the field of population administration in Tanggulangin District, Sidoarjo Regency has applied the dimensions of physical evidence (tangible), aspects of reliability, aspects of responsiveness, aspects of assurance, and aspects of empathy which cover all discussion of indicators, but there are a few indicators that run according to the wishes of the community. in this study to improve the quality of public services in Tanggulangin District, Sidoarjo Regency, namely Human Resources (HR), public awareness, facilities and infrastructure.